2023
DOI: 10.1037/xge0001367
|View full text |Cite
|
Sign up to set email alerts
|

Not what u expect: Effects of prediction errors on item memory.

Abstract: The characterization of the relationship between predictions and one-shot episodic encoding poses an important challenge for memory research. On the one hand, events that are compatible with our previous knowledge are thought to be remembered better than incompatible ones. On the other hand, unexpected situations, by virtue of their novelty, are known to cause enhanced learning. Several theoretical accounts try to solve this apparent paradox by conceptualizing prediction error (PE) as a continuum ranging from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Findings reported in a separate publication using the same data as the current study 26 showed that such context manipulation affected recognition memory. Specifically, memory was found to be better for contexts characterized by weaker expectations, compared to contexts in which expectations were stronger.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Findings reported in a separate publication using the same data as the current study 26 showed that such context manipulation affected recognition memory. Specifically, memory was found to be better for contexts characterized by weaker expectations, compared to contexts in which expectations were stronger.…”
Section: Introductionsupporting
confidence: 78%
“…For a more detailed description of the materials and methods used, please refer to the original publication 26 . For Experiment 1, six coloured scene categories depicting real-world outdoor locations were taken from the ECOS database (https://sites.google.com/ view/ecosdatabase/) were used as contexts (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the best-fitting model for our analysis, we used a backward selection method (Barr, 2013;Ortiz-Tudela, Nolden, et al, 2023). We began with the most complex model that included age group, ending type and their interaction as fixed effects, and independent slopes and intercepts for participants and comic strips as random effects.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between episodic memory and the anticipation of future states is far from unidirectional. It has been proposed that predictive processing might have a critical role on shaping how our brains store episodic information (Brod, 2021;Brod et al, 2022;Ortiz-Tudela, Nolden, et al, 2023;Quent et al, 2022;van Kesteren et al, 2012). In the current study, we attempted to jointly characterise the effect of expectedness on four different features of the retrieved episode.…”
Section: Prediction (Error) Impacts Different Aspects Of the Encoded ...mentioning
confidence: 99%
“…Prediction error often leads to better learning (Quent et al, 2021; Stawarczyk et al, 2020), and surprising actions are recognized more accurately than actions that are consistent with a particular situation (Ben-Yakov et al, 2021). Nevertheless, the relationship between prediction error and memory performance is complex; in some studies, both particularly high and low prediction error can benefit memory, while intermediate levels confer no advantage (Greve et al, 2019), yet in other studies, the opposite pattern is found (Ortiz-Tudela et al, 2023). In addition, there is a large literature showing that in many situations, events that are congruent with prior knowledge are better remembered (Bein et al, 2014; Brod & Shing, 2019; Craik & Tulving, 1975; Gilboa & Marlatte, 2017; Ortiz-Tudela et al, 2017; Raykov et al, 2021).…”
Section: The Present Experimentsmentioning
confidence: 99%